1987
DOI: 10.1111/j.1365-2044.1987.tb05278.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypolgcaemic encephalopathy following surgery on phaeochromocytoma

Abstract: Key wordsC'n~~ii)/ic.citioiis; hypoglycaemic encephalopathy. S~i r g c q~; p haeoch ro niocy t oina reinova I.Many coinplications that follow surgery on phaeochromocytoma have been reported and mainly concern bleeding. haemodynamic disturbances. cardiac dysrhythmias and fluid balance problems. Phaeochromocytoma is also associated with a diabetic syndrome that presents with hyperglycaemia both pre-and postoperatively.However, some patients may develop hypoglycaemia d uring surgery and immediately postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Six patients in our series developed severe hypoglycemia 2M 1 hours (3 hours on average) after removal of the pheochromocytoma, this result being in accordance with the interval reported in the literature (i.e., 0-4 hours) with 1~ hours on average after the end of the surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The plasma IRI level was at a maximum at about 1 hour; and the plasma glucose level was at the nadir about 3 hours after the tumor excision.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Six patients in our series developed severe hypoglycemia 2M 1 hours (3 hours on average) after removal of the pheochromocytoma, this result being in accordance with the interval reported in the literature (i.e., 0-4 hours) with 1~ hours on average after the end of the surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The plasma IRI level was at a maximum at about 1 hour; and the plasma glucose level was at the nadir about 3 hours after the tumor excision.…”
Section: Discussionsupporting
confidence: 86%
“…Hyperglycemia is also a common preoperative disorder associated with pheochromocytomas. It is surprising, however, that there have been only 16 reported cases of severe hypoglycemia following removal of a pheochromocytoma [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…If unrecognized, hypoglycemia can have severe neurologic consequences. 4 In this study, we aim to further describe the incidence and characteristics of postoperative hypoglycemia after pheochromocytoma resection and to identify risk factors for the development of this complication.…”
mentioning
confidence: 99%
“…Although most patients recover quickly with intravenous glucose therapy, careful monitoring is mandatory, because hypoglycemia could be prolonged 6 or recurrent 7 and cause severe neurological complications. 8 A study of the perioperative complications of pheochromocytoma resection reported that 15% of the patients developed post-excisional hypoglycemia and required intensive glucose therapy; 9 other studies reported a similar incidence of post-excisional hypoglycemia (13.3% with hypoglycemia defined as serum glucose levels <50 mg/ dL 3 and 4.2% with hypoglycemia defined as serum glucose levels <55 mg/dL 4 ) as the present study, suggesting that postexcisional hypoglycemia is a common complication after surgery for pheochromocytoma. These consistent results highlight the importance of careful monitoring of serum glucose levels during and after pheochromocytoma resection.…”
Section: Discussionmentioning
confidence: 99%